2017
DOI: 10.1111/auar.12134
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking and Learning in Public Healthcare: Properties and Effects

Abstract: This research investigates the effects of learning-oriented benchmarking in public healthcare settings. Benchmarking is a widely adopted yet little explored accounting practice that is part of the paradigm of New Public Management. Extant studies are directed towards mandated coercive benchmarking applications. The present study analyses voluntary benchmarking in a public setting that is oriented towards learning. The study contributes by showing how benchmarking can be mobilised for learning and offers eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
1
1
Order By: Relevance
“…Anonymity is what the firms wanted in order to participate. This is contrary to what literatures on benchmarking say about the usefulness of ranking, which is that it is conditional on the active comparison with identifiable others who differ in the ranking (Booth et al, 2005;Buckmaster & Mouritsen, 2017;Laine & Vinnari, 2014). Learning happens not vis-avis oneself but vis-a-vis others.…”
Section: Which Anxiety?contrasting
confidence: 65%
“…Anonymity is what the firms wanted in order to participate. This is contrary to what literatures on benchmarking say about the usefulness of ranking, which is that it is conditional on the active comparison with identifiable others who differ in the ranking (Booth et al, 2005;Buckmaster & Mouritsen, 2017;Laine & Vinnari, 2014). Learning happens not vis-avis oneself but vis-a-vis others.…”
Section: Which Anxiety?contrasting
confidence: 65%
“…(2002) found that benchmarking in the private and public sectors differs, because benchmarking in the private sector is voluntary, whereas benchmarking in the public sector tends to be compulsory and implemented from the top down in an attempt to increase accountability and improve efficiency. However, for exceptions, see Buckmaster and Mouritsen (2017) as well as Laine and Vinnari (2014). Furthermore, the use of benchmarking in the private sector differs from the public sector in that the results are mostly kept confidential for competitive reasons and are often facilitated by a trusted third party.…”
Section: Trust and Learning In Benchmarking Networkmentioning
confidence: 99%